2006
DOI: 10.1158/1535-7163.mct-06-0242
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule-targeting agents inhibit angiogenesis at subtoxic concentrations, a process associated with inhibition of Rac1 and Cdc42 activity and changes in the endothelial cytoskeleton

Abstract: Conventional anticancer agents may display antiangiogenic effects, but the underlying mechanism is poorly understood. We determined the antiangiogenic properties of cisplatin, doxorubicin, and the microtubule-targeting agents docetaxel, epothilone B, and vinblastine at concentrations not affecting cell proliferation. We also assessed tubulin and actin morphology and the activity of two key molecules in cell motility, the small Rho GTPases Cdc42 and Rac1. The highest non-toxic concentration (HNTC) of each drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
90
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(109 citation statements)
references
References 36 publications
17
90
0
2
Order By: Relevance
“…The significance of the effects of epothilone B on α-actinin 4 are underscored by results from a recent study where we demonstrated that α-actinin 4 displayed significantly higher protein levels in high grade (III-IV) glioblastomas as compared to normal brain tissue (16). Furthermore, our results are consistent with studies undertaken by hayot et al (33) and Bijman et al (22), who also demonstrated that microtubule targeting agents invoked reduced endothelial cell motility as a consequence of actin-reorganization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The significance of the effects of epothilone B on α-actinin 4 are underscored by results from a recent study where we demonstrated that α-actinin 4 displayed significantly higher protein levels in high grade (III-IV) glioblastomas as compared to normal brain tissue (16). Furthermore, our results are consistent with studies undertaken by hayot et al (33) and Bijman et al (22), who also demonstrated that microtubule targeting agents invoked reduced endothelial cell motility as a consequence of actin-reorganization.…”
Section: Discussionsupporting
confidence: 92%
“…6B, D and F). These data parallel findings seen in endothelial (22) and breast cancer (23) cells, which also underwent filamentous actin reorganization in response to treatments with microtubule inhibiting agents. Immunoblotting experiments revealed that exposure of glioblastoma cells to epothilone B had no effect on α-actinin 4 protein levels (Fig.…”
Section: Resultssupporting
confidence: 82%
“…The migration assay used was a monolayer denudation assay as described by Marcel et al (25). Briefly, confluent HUVEC in 24-well plates (Costar, America) were mechanically "wounded" by scraping away a swath of cells with a pipette tip and denuding a strip of the monolayer 300 μm wide.…”
Section: Migration Assaymentioning
confidence: 99%
“…Thus, microtubule-interfering agents such as Vinca alkaloids and taxanes are widely used in the treatment of hematological malignancies and solid tumors. Furthermore, recent studies have indicated that microtubules regulate cell motility in close collaboration with actin fibers [4] and that microtubule-interfering agents can impair angiogenesis within a tumor by inhibiting endothelial cell motility rather than proliferation [5]. These findings suggest microtubule-interfering agents at non-toxic doses may be used to disrupt tumor vasculature and prevent tumor progression.…”
Section: Introductionmentioning
confidence: 99%